Somatosensory evoked potentials recorded from DBS electrodes: the origin of subcortical N18 : neurology and preclinical neurological studies - Abdulbaki, Arif; Wöhrle, Johannes C.; Blahak, Christian; Weigel, Ralf; Kollewe, Katja; Capelle, H. Holger; Bäzner, Hansjörg; Krauss, Joachim K. (Journal of neural transmission, 2024)
The different peaks of somatosensory-evoked potentials (SEP) originate from a variety of anatomical sites in the central nervous system. The origin of the median nerve subcortical N18 SEP has been studied under various conditions, but the exact site of its generation is still unclear. While it has been claimed to be located in the thalamic region, other studies indicated its possible origin below the pontomedullary junction. Here, we scrutinized and compared SEP recordings from median nerve stimulation through deep brain stimulation (DBS) electrodes implanted in various subcortical targets. We studied 24 patients with dystonia, Parkinson’s disease, and chronic pain who underwent quadripolar electrode implantation for chronic DBS and recorded median nerve SEPs from globus pallidus internus (GPi), subthalamic nucleus (STN), thalamic ventral intermediate nucleus (Vim), and ventral posterolateral nucleus (VPL) and the centromedian-parafascicular complex (CM-Pf). The largest amplitude of the triphasic potential of the N18 complex was recorded in Vim. Bipolar recordings confirmed the origin to be close to Vim electrodes (and VPL/CM-Pf) and less close to STN electrodes. GPi recorded only far-field potentials in unipolar derivation. Recordings from DBS electrodes located in different subcortical areas allow determining the origin of certain subcortical SEP waves more precisely. The subcortical N18 of the median nerve SEP—to its largest extent—is generated ventral to the Vim in the region of the prelemniscal radiation/ zona incerta.